2018
DOI: 10.1038/s41598-018-20076-y
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of diffusion tensor imaging of substantia nigra in patients with Parkinson’s disease

Abstract: Parkinson’s disease (PD) is a common neurodegenerative disease characterized by severe, selective loss of pigmented neurons in the substantial nigra (SN). Previous studies have indicated that such loss could be detected by diffusion tensor imaging (DTI). Here, we try to consolidate current DTI data to both quantitatively determine the imaging changes in SN, as well as explore the potential use of DTI for PD diagnosis. Fourteen research articles are included in this meta-analysis, each obtained by searching Pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
1
29
0
1
Order By: Relevance
“…TheT2 weighted images capture the elevated levels of iron mainly in SNr (Du et al, ; Langley et al, ; Langley et al, ; Langley, Huddleston, Sedlacik, Boelmans, & Hu, ). A study by Langley et al demonstrated that T2‐weighted and NMS‐MRI are sensitive to different sub regions of SN (Langley et al, ), and the hypo‐intensity observed on T2 images is unreliable in localizing SNc (Deng et al, ; Langley et al, ; Wypijewska et al, ). A recent study also demonstrated that increase in T2* weighted hypo intense signal is an indication of increase in iron deposition related to PD pathology (Langley et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TheT2 weighted images capture the elevated levels of iron mainly in SNr (Du et al, ; Langley et al, ; Langley et al, ; Langley, Huddleston, Sedlacik, Boelmans, & Hu, ). A study by Langley et al demonstrated that T2‐weighted and NMS‐MRI are sensitive to different sub regions of SN (Langley et al, ), and the hypo‐intensity observed on T2 images is unreliable in localizing SNc (Deng et al, ; Langley et al, ; Wypijewska et al, ). A recent study also demonstrated that increase in T2* weighted hypo intense signal is an indication of increase in iron deposition related to PD pathology (Langley et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have employed T2 weighted, proton density weighted spin echo and inversion recovery based contrasts to precisely localize the SNc ROIs (Atasoy et al, 2004;Duguid, De La Paz, & DeGroot, 1986;Geng, Li, & Zee, 2006;Hutchinson & Raff, 2000;Oikawa, Sasaki, Tamakawa, Ehara, & Tohyama, 2002;Pujol, Junque, Vendrell, Grau, & Capdevila, 1992;Stern, Braffman, Skolnick, Hurtig, & Grossman, 1989;Tuite, Mangia, & Michaeli, 2013). However, in a conventional T2 weighted MRI, there is variability in the hypo-intensity associated with the SNc as a result of increased iron deposition, in addition to the reduction in neuromelanin content (Deng, Wang, Yang, Li, & Yu, 2018;Langley et al, 2015;Langley et al, 2016;Wypijewska et al, 2010). This often leads to an inaccurate marking of SNc boundaries and a false pathological representation of dopamine degeneration (Langley et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier DTI studies on PD have been based on contrast obtained from T2 weighted images (Du et al, 2011;Langley et al, 2016;Prakash et al, 2012;Rolheiser et al, 2011;Schwarz et al, 2013;Vaillancourt et al, 2009). Comparative studies (Du et al, 2011;Langley et al, 2015)on contrast generating MR sequence for SNc have shown that T2w sequences and NMS-MRI sequences are both sensitive to different sub regions of SNc, although hypo-density observed on T2 images in PD could also indicate iron deposition apart from dopaminergic loss in the SNc, making it highly unreliable (Deng et al, 2018;Langley et al, 2016;Wypijewska et al, 2010). Recent work by Visser et al (Visser et al, 2016) has employed the FLASH sequence on 7T MRI to delineate the substantia nigra.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the techniques employed for delineating the SNc may have a significant bearing on the variability in the observed results. For instance, in a conventional T2 weighted MRI, there is variability in the hypointensity associated with the SNc as a result of increased iron deposition, in addition to the reduction in neuromelanin content (Deng, Wang, Yang, Li, & Yu, 2018;Langley et al, 2016;Wypijewska et al, 2010).This often leads to an inaccurate marking of SNc boundaries, false pathological representation of dopamine degeneration and also a poor contrast of the SNc (Langley et al, 2016). Diffusion tractography based techniques to localize the SNc are more complicated and may depend upon the choice of diffusion MRI protocol and the fiber tracking algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…We used the Newcastle-Ottawa Scale (NOS) criteria to assess the quality of all included studies [5]. Three studies showed high quality (≥8 points) [6], and all studies scored six points or more according to the NOS criteria, indicating the quality of all included studies was good [7]. Any disagreements on the quality assessment and data extraction would be resolved by consensus or consultation of a third party.…”
Section: Methodsmentioning
confidence: 99%